Factors explaining failure to suppress viral load in pregnant women living with HIV in Mbandaka, Equateur Province (Democratic Republic of Congo) - Jean Claude Efoloko Likulu; Jules Moti Kangite; Freddy Adu Adikaka; Tonton Manga Bosako; Patrick Bongbanga Mundembe; Guillain Boboko Bikoko; Richard Bikopo Betoko; Monizi Mawunu; Jean-Paul Koto-Te-Nyiwa Ngbolua; Félicien Kandolo Tshimungu; Jean Pierre Moyene Elongi (Orapuh Journal)
Introduction